Dietary Inclusion of Hydrolyzed Debaryomyces Hansenii Yeasts Modulates Physiological Responses in Plasma and Immune Organs of Atlantic Salmon (Salmo Salar) Parr Exposed to Acute Hypoxia Stress - Imarai-Bahamonde, C (Frontiers Media S.A., 2022)
Stress related to salmon aquaculture practices (handling, sub-optimal nutrition, diseases, and environmental problems) may compromise fish welfare. This study describes the effects of two hydrolyzed Debaryomyces hansenii yeast-based products (LAN4 and LAN6) on physiological and immune responses of Atlantic salmon (Salmo salar) parr exposed to short hypoxia stress. A commercial-like diet (control diet: CD) and two experimental diets (CD supplemented with 0.1% of either component LAN4 or LAN6) were fed to fish for 8 weeks. At the end of the feeding experiment, fish were exposed to 1-min hypoxia and samples were collected at 0, 1, 3, 6, 12, and 24 h post-stress. Results showed that plasma cortisol reached a peak at 1 h post-stress in CD and LAN6 groups, whereas no significant increase in cortisol levels was detected in the LAN4 group. Moreover, the LAN6 group enhanced IL-10 responses to hypoxia, when compared to the control and LAN4 group. This suggests a regulation of immunosuppressive profiles in fish fed LAN4. Hypoxia stress increased TNFα in all groups, which indicates that fish may compensate for the short-term stress response, by modulating innate immune molecules. The apparent suppression of hypoxia responses in the LAN4 group coincided with the detection of differences in goblet cells size and Muc-like proteins production in DI; and upregulation (1 h post-stress) of pathways related to oxygen transport, hemoglobin complex, and glutathione transferase activity and the downregulation of fatty acid metabolism (6 h post-stress) in gills. To conclude, a 1-min hypoxia stress exposure affects the response to stress and immunity; and D. hansenii-based yeast products are promising components in functional aquafeeds for salmon due to their ability to counteract possible consequences of hypoxic stress. Copyright © 2022 Morales-Lange, Djordjevic, Gaudhaman, Press, Olson, Mydland, Mercado, Imarai, Castex and Øverland.